2019
DOI: 10.1024/0301-1526/a000771
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary team decision is rare and decreasing in percutaneous vascular interventions despite positive impact on in-hospital outcomes

Abstract: Abstract. Background: Worldwide prevalence of peripheral artery disease (PAD) is increasing and peripheral vascular intervention (PVI) has become the primary invasive treatment. There is evidence that multidisciplinary team decision-making (MTD) has an impact on in-hospital outcomes. This study aims to depict practice patterns and time changes regarding MTD of different medical specialties. Methods: This is a retrospective cross-sectional study design. 20,748 invasive, percutaneous PVI of PAD conducted in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Multidisciplinary “foot teams” following the role model of previously established “heart teams” may be an appropriate way to follow the recommendations for a stepwise care system. Unfortunately, there is striking data suggesting that multidisciplinary team discussions are still the Achilles heel of PAOD treatment [ 34 ]. To provide more data for the establishment of evidence-based therapy, future studies should avoid an exclusion of patients with concomitant CKD or ESKD as there was a severity dependent increase of the incidence of adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Multidisciplinary “foot teams” following the role model of previously established “heart teams” may be an appropriate way to follow the recommendations for a stepwise care system. Unfortunately, there is striking data suggesting that multidisciplinary team discussions are still the Achilles heel of PAOD treatment [ 34 ]. To provide more data for the establishment of evidence-based therapy, future studies should avoid an exclusion of patients with concomitant CKD or ESKD as there was a severity dependent increase of the incidence of adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, three different medical specialties were almost equally involved in the endovascular procedures, emphasizing the importance to include all specialties in data collections on endovascular treatments. Against that backdrop it appears noteworthy to highlight that all valid practice guidelines recommend a multidisciplinary approach but there is evidence suggesting an insufficient adherence concerning multidisciplinary team decisions in PAD treatment [22]. From 2013 through 2014, the German national registry for first line treatment strategies in patients with critical limb ischemia (CRITISCH register) collected multicentre data on 1200 patients suffering from CLTI from 27 selected centres.…”
Section: Discussionmentioning
confidence: 99%
“… 95 ) Behrendt et al promoted multidisciplinary team decision-making, which contributed to the technical success of peripheral vascular interventions and better in-hospital outcomes. 96 ) Kolte et al recently reported that a vascular team approach has the potential to significantly enhance quality of care, improve clinical outcomes, and reduce costs. 97 ) In addition to a vascular team, vascular nursing has been determined to be an important option that will provide a comprehensive approach to the treatment of patients with various vascular diseases.…”
Section: Potential Treatment or Strategy For Frailty And Sarcopenia I...mentioning
confidence: 99%